Promoviendo el comercio de cultivos nativos para mejorar los medios de vida rurales en los Andes - Devaux, A.; Ordinola, M.; Andrade-Piedra, J.L.; Thiele, Graham (Asociacion Latinoamericana de la Papa, 2020)
Native potato production is an important livelihood strategy for most rural Andean families. An inclusive value chain development approach developed by the International Potato Center (CIP) triggered innovation processes to enhance the marketing of native potatoes benefiting small-scale producersand value chain actors and improving their livelihoods.Making use of new market opportunities for development requiresan array of other innovationsincluding institutional and technologicalones. The approach initially developed in Peru was also successfully implemented in Ecuador and Boliviaandcould be expandedto other crops in other regions.